2014
DOI: 10.1039/c4ra05211k
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analyses of the fluorescence lifetimes of thed-amino acid oxidase–benzoate complex dimer from porcine kidney: molecular dynamics simulation and photoinduced electron transfer

Abstract: The mechanism of photoinduced electron transfer from benzoate and aromatic amino acids to the excited isoalloxazine in the d-amino acid oxidase–benzoate complex dimer was studied using molecular dynamics simulation and an electron transfer theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…The catalytic pockets dynamic revealed to be rather different from the crystallographic data in both wt proteins, more pronounced in the side‐chain conformations of the catalytic residue E376 and R256 residue in the presence of the fatty‐acyl substrate. Differences between the crystallographic and the MD structures have been also reported in other flavoproteins .…”
Section: Discussionmentioning
confidence: 77%
“…The catalytic pockets dynamic revealed to be rather different from the crystallographic data in both wt proteins, more pronounced in the side‐chain conformations of the catalytic residue E376 and R256 residue in the presence of the fatty‐acyl substrate. Differences between the crystallographic and the MD structures have been also reported in other flavoproteins .…”
Section: Discussionmentioning
confidence: 77%
“…In the crystal the two subunits were almost completely equivalent (Suto et al, 2000;Taniguchi et al, 2013). In the D-amino acid oxidase (DAAO) from porcine kidney À benzoate complex (DAOB) dimer, it was also found that the structures of the two subunits near Iso were not equivalent, as revealed by the MDS technique (Nueangaudom et al, 2014a), which was predicted by experimental work on the fluorescence dynamics . In the crystal, the two subunits in the DAOB dimer were almost equivalent (Nueangaudom et al, 2014a;Mizutani et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…In the D-amino acid oxidase (DAAO) from porcine kidney À benzoate complex (DAOB) dimer, it was also found that the structures of the two subunits near Iso were not equivalent, as revealed by the MDS technique (Nueangaudom et al, 2014a), which was predicted by experimental work on the fluorescence dynamics . In the crystal, the two subunits in the DAOB dimer were almost equivalent (Nueangaudom et al, 2014a;Mizutani et al, 1996). Pyranose 2-oxidase from Trametes multicolor is a tetramer, and an ultrafast fluorescence dynamics experiment revealed that there exist two lifetime components, 0.88 ps and 360 ps, which shows that the protein structure near Iso is extremely heterogeneous Taniguchi et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The SHAKE algorithm [52] was employed to constrain all bonds involving hydrogen atoms. Details of the methods are described elsewhere [53][54][55][56].…”
Section: Mds Calculationsmentioning
confidence: 99%